Death by electrocution: a retrospective analysis of three medico-legal mortuaries in the eThekwini district of KwaZulu Natal from 2006 to 2016. - Awath- Behari, Anez (Department of Pathology, 2023)
Background: Electrocution is a well-documented cause of unnatural death globally. Identification of demographic and spatial trends in developed countries has assisted in highlighting contributing factors and identifying areas at risk. This information and the appropriate institution of changes have proven worthwhile in reducing fatalities internationally. Less developed countries have shown increasing trends in electrocution fatalities related to rural-urban migration and growing electricity demand. Additional challenges plaguing such countries include illegal electricity connections and load shedding. The association of such issues to electrocution deaths have been sparsely explored. There remains a paucity of information regarding electrocution fatalities in South Africa and Africa as a whole. A general trend of increasing electrocution fatalities referred for medico-legal autopsy was observed at three medico-legal mortuaries in the eThekwini district of Kwa Zulu Natal, South Africa, from 2006 to 2016. Objectives This study aimed to analyse the epidemiology, characteristics and trends of deaths resulting from electrocutions. Methods. A retrospective descriptive study was conducted. Fatal non-lightning electrocutions autopsied at three medico-legal mortuaries in the eThekwini district over an 11year period, from 1st January 2006 to 31st December 2016, were analysed. Data sources included clinician notes, emergency services documentation, scene scripts including South African Police Services(SAPS) 180 form completed by SAPS representatives, postmortem and histology reports, toxicology reports from Forensic Toxicology unit, contemporaneous notes, postmortem death registers, daily listings of postmortem case allocations and electronic postmortem databases. Data were collated and categorised on an Excel spreadsheet and then analysed on statistical package STATA 13 (Stata Corp, TX, USA). 12 Results: There were 512 non-lightning electrocution fatalities from 1 st January 2006 to 31st December 2016. The trend of electrocutions indicates a general increase in cases from 2006, reaching a peak in 2013 followed by a gradual decrease until 2016. Most fatal electrocutions occurred in domestic environments amongst males in the third and fourth decade of life. However, a bimodal distribution showed a considerable number of electrocutions under 10 years of age, predominantly amongst females. The largest number of electrocutions were admitted to the chief medico-legal mortuary servicing the metro, Gale Street mortuary (43,95%). However, the highest concentration of cases was observed in Tongaat, a suburb on the outskirts of the metro. This contributed to the highest prevalence of electrocution cases (1,25% of all electrocution cases) being admitted to the Phoenix medico-legal mortuary, which serves predominantly Northern eThekwini, including Tongaat, and which lies on the fringe of the metro. Deaths from electrocution tend to occur mainly during the midday period, during the weekends, and commonly during the summer months. Injuries associated with fatal electrocutions in all age groups studied generally affected the extremities and predominantly involved the upper limbs. Blood alcohol concentrations were established in just over a quarter of cases and were mostly negative. Conclusion: Electrocution is an easily preventable unnatural death that remains poorly documented and analysed, especially in developing countries, with a paucity of studies in South Africa. Preventative measures and protocols cannot be generalised amongst populations. An appreciation of the demographic and temporal trends of electrocutions is crucial in order to institute preventative policy.